1994
DOI: 10.1039/fd9949900341
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of chirality in second-order non-linear spectroscopy at surfaces

Abstract: Surface second-harmonic generation (SHG) is recognized as a second-order non-linear laser-based spectroscopy offering good surface sensitivity and selectivity. With the goal of developing optical methods to study chiral surfaces, a way to detect dichroic behaviour in SHG in analogy to circular dichroism (CD) spectroscopy has been elucidated. The SHG efficiency from a monolayer of oriented chiral molecules [(R)or (S)-2,2'-dihydroxy-1,l'-binaphthyl (BN)] has a strong dependence upon whether the excitation beam h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…For this purpose, we must search for a microscopic understanding of chirality at molecular level. Theoretical works on nonlinear optical activity of chiral molecules are rare [6][7][8] and most of them are limited to ab initio calculations. They fail to provide a clear physical picture relating the results to the molecular chiral structure.…”
mentioning
confidence: 99%
“…For this purpose, we must search for a microscopic understanding of chirality at molecular level. Theoretical works on nonlinear optical activity of chiral molecules are rare [6][7][8] and most of them are limited to ab initio calculations. They fail to provide a clear physical picture relating the results to the molecular chiral structure.…”
mentioning
confidence: 99%
“…One striking optical manifestation of planochirality is a large circular intensity difference in second-harmonic light scattering from chiral molecules on an isotropic surface [64]. Because the mechanism involves pure electric dipole interactions, the effect is three orders of magnitude larger than analogous phenomena observed in the bulk since the latter require interference between electric dipole and magnetic dipole interactions [2].…”
Section: Chirality In Two Dimensionsmentioning
confidence: 99%
“…However, it can probe the chirality of anisotropic systems such as chiral surfaces, as first demonstrated by Hicks group [8,9,10,11,12]. Reviews on SHG as a probe for surface chirality can be found in references [13,14,15].…”
Section: Sum-frequency Generation As a Probe Of Chiralitymentioning
confidence: 99%